2005
DOI: 10.1038/sj.bmt.1704938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disease burden at time of allogeneic stem cell transplantation in adults with acute myeloid leukemia and myelodysplastic syndromes

Abstract: Summary:The impact of disease burden on the outcome of patients with acute myeloid leukemia (AML) undergoing allogeneic stem cell transplantation (SCT) has not been well defined. Data from several retrospective series suggest that overt leukemia at the time of transplant increases the risk of relapse. We reviewed the outcomes of 68 consecutive adults with AML (n ¼ 60) or myelodysplastic syndromes (MDS) (n ¼ 8) who received an allogeneic SCT at the University of Chicago between May 1986 and October 2002 to conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…However, if leukemic blasts is present-even in small numbers-their presence in the BM (tumor burden) is associated with poorer outcome, irrespective of morphologic blast count. 14,15,42 This is particularly applicable for RIC allo-HCT. 11,21,[43][44][45] We observed a reduced risk of relapse in CMV seropositive recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if leukemic blasts is present-even in small numbers-their presence in the BM (tumor burden) is associated with poorer outcome, irrespective of morphologic blast count. 14,15,42 This is particularly applicable for RIC allo-HCT. 11,21,[43][44][45] We observed a reduced risk of relapse in CMV seropositive recipients.…”
Section: Discussionmentioning
confidence: 99%
“…9 It is clear that patients with active leukemia had more relapse and worse OS after allo-HCT regardless of donor type or patient age. [10][11][12][13][14][15] Following allo-HCT, 40-60% of AML patients in CR1 enjoy long-term OS, whereas o20% of refractory or relapsed AML patients survive. 1,11 Yet even for allo-HCT during CR, relapse remains the most frequent complication of allo-HCT.…”
Section: Introductionmentioning
confidence: 99%
“…12,32,[39][40][41] The presence of active disease at the time of transplantation remained the strongest predictor of inferior transplant outcome, indicating that this cohort of patients should be considered for alternative therapeutic strategies. The role of dose-escalated conditioning regimens or sequential chemotherapy followed by RIC HSCT has been investigated by other groups in this context, with promising results.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] Recent literature has indicated that performance status of transplant recipients, rather than recipient age per se, may be a better indicator of the ability of a patient to tolerate allo-HSCT. The Charlson comorbidity index, adapted for HSCT, has been shown to predict NRM in patients receiving allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…50,51 In contrast, the prognostic role of pre-HCT MRD in non-APL AML is primarily studied via MFC-based assays to detect and quantify MRD. 46,47,[52][53][54][55][56][57][58][59][60][61] Nevertheless, as summarized in Table 4, more recent series show that both pediatric and adult patients with non-APL AML who are MRD À by current sensitive methods have excellent outcomes following myeloablative AlloHCT, with 2-5 year OS estimates around 75-80%. 47,58,61 For such patients, even AutoHCT may result in good disease control, with some studies showing 5-year OS estimates in the 60-70% range.…”
Section: The Concept and Determination Of Mrdmentioning
confidence: 99%